Investigation of structural and electrical transport properties of nano-flower shaped NiCo2O4 supercapacitor electrode materials - Karmakar, Subrata; Varma, Shikha; Behera, Dhrubananda (Journal of alloys and compounds, 2018)
Nickel cobaltite nano-flower was synthesized via temperature dependent co-precipitation techniques and its single phase formation, vibrational spectra and nanostructured with flower-like morphology were confirmed by XRD, FTIR, Raman and TEM micrographs. The electrical transport properties and conduction mechanism of NiCo2O4 were studied first time using complex impedance spectroscopy in frequency range 100 Hz-1 MHz and wide temperature range 25 °C-300 °C. Poor grain relaxation was observed from RT to 75 °C whereas interface (both grain boundary and electrode effect) plays a dominant role above 75 °C are ascertained from Nyquist plot of impedance and modulus spectra. The utmost dielectric constant (6.8 × 102) and loss (540) was observed at high temperature (300 °C) and low frequency (100 Hz) regime and gradually diminished with high-frequency evolution and low-temperature approach. Finally, the ac and dc conduction mechanism were examined individually in details by the help of hooping relaxation model and overlapping large polaron tunneling (OLPT) concept for supercapacitor application. The calculated value of activation energy for dc conduction (0.63 eV) is larger than ac conduction (0.36 eV) as the ac conductivity is thermally activated. •Nickel Cobaltite (NiCo2O4) nano-flower was prepared via Co-precipitation techniques.•Grain, grain boundary and electrode interface effect were explained by impedance and modulus spectra.•The dielectric constant and loss relaxes with dispersion of higher frequency.•Conduction mechanism was examined by hopping relaxation model and OLPT concept.